Activation Barriers for Cobalt(IV)-Centered Reductive Elimination Correlate with Quantified Interatomic Noncovalent Interactions - Loir-Mongazon, Lucas; Antuña-Hörlein, Carmen; Deraedt, Christophe; Cornaton, Yann; Djukic, Jean-Pierre (Synlett, 2022)
In this joint theoretical and experimental study, an analysis of weak interligand noncovalent interactions within Co(IV) [Cp*Co(phpy)X]+ cobaltacycles (phpy = 2-phenylenepyridine, κC,N) was carried out by using the independent gradient model/intrinsic bond strength index (IGM/IBSI) method to evaluate the dependency of the catalytically desired reductive elimination pathway (RE) on the nature of the X ligand. It is shown that the barrier for activation of the RE pathway correlates directly with the IBSI of the X-to-carbanionic chelate’s carbon. This correlation suggests that in silico prediction of which X ligand is more prone to operate an efficient Cp*Co-catalyzed directed X-functionalization of an aromatic C–H bond is attainable. A set of experiments involving various sources of X ligands supported the theoretical conclusions.
Keywords: metallacycles; cobalt catalysis; density functional theory; noncovalent interactions; reductive elimination; C–H bond activation